2018
DOI: 10.3390/jimaging4030046
|View full text |Cite
|
Sign up to set email alerts
|

Feature Importance for Human Epithelial (HEp-2) Cell Image Classification

Abstract: Indirect Immuno-Fluorescence (IIF) microscopy imaging of human epithelial (HEp-2) cells is a popular method for diagnosing autoimmune diseases. Considering large data volumes, computer-aided diagnosis (CAD) systems, based on image-based classification, can help in terms of time, effort, and reliability of diagnosis. Such approaches are based on extracting some representative features from the images. This work explores the selection of the most distinctive features for HEp-2 cell images using various feature s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Image classification using classification algorithms and learning-based algorithms have been implemented for a wide range of applications and scales. From the landscape scale, such as classification of land use and plant ecological units (co-occurring plant species) based on multi-spectral satellite imagery [28,29,30], to the hand specimen scale, such as medical image detection and diagnosis of radiology data [31], and reaching the microscopical scale, such as cell image classification for medical diagnose [32].…”
Section: Introductionmentioning
confidence: 99%
“…Image classification using classification algorithms and learning-based algorithms have been implemented for a wide range of applications and scales. From the landscape scale, such as classification of land use and plant ecological units (co-occurring plant species) based on multi-spectral satellite imagery [28,29,30], to the hand specimen scale, such as medical image detection and diagnosis of radiology data [31], and reaching the microscopical scale, such as cell image classification for medical diagnose [32].…”
Section: Introductionmentioning
confidence: 99%
“…The prediction of visual attention data from any type of media is valuable to content creators and is used to drive coding algorithms effectively. With the current trend in the field of virtual reality (VR), the adaptation of known technologies to this new media is beginning to gain momentum R. Gupta and Bhavsar [6] proposed an extension to the architecture of any convolutional neural network (CNN) to fine-tune traditional 2D significant prediction to omnidirectional image (ODI). In an end-to-end manner, it is shown that each step in the pipeline presented by them is aimed at making the generated salient map more accurate than the ground live data.…”
Section: Introductionmentioning
confidence: 99%